If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 = 9(2f + 5) Reorder the terms: 7 = 9(5 + 2f) 7 = (5 * 9 + 2f * 9) 7 = (45 + 18f) Solving 7 = 45 + 18f Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-18f' to each side of the equation. 7 + -18f = 45 + 18f + -18f Combine like terms: 18f + -18f = 0 7 + -18f = 45 + 0 7 + -18f = 45 Add '-7' to each side of the equation. 7 + -7 + -18f = 45 + -7 Combine like terms: 7 + -7 = 0 0 + -18f = 45 + -7 -18f = 45 + -7 Combine like terms: 45 + -7 = 38 -18f = 38 Divide each side by '-18'. f = -2.111111111 Simplifying f = -2.111111111
| 3(2x+3)=4-x | | 4w-7=3w+1 | | x^2+18x+30=0 | | 4x-5=4x-9 | | 1/2n+5/6=2/3 | | (6x+2)+20=90 | | -8-7x-6x=-8 | | 18=a(a-7) | | 4x=14x-30 | | 6b+15=4b+19 | | -84=-7(x+5) | | (6x+2)+20=360 | | 20+.5= | | bing=-2 | | -20=-4x+-6x | | -5.6+12.2=5 | | 2x+3(2x-9)=(4x+3) | | (6x+2)+20=180 | | 5a+6=-8 | | 8x-2x+66=8x+26 | | 2y-4=-10x | | 5y-60332=600y+422 | | -7+2h=-15 | | 2(4b-6)+6(-3-2b)=6-4b+4-5b | | 3x+9=-6x+16 | | 4x+6=y-3 | | 8u+1=7u+1 | | 4k-2=k-6 | | 15+.25x= | | 3(2x+1)=5(x-4) | | 5(b-6)=3(b+4) | | x+y=4x |